Gunshots from the Inside - Writers in the Community (2015)
Number of pages: 16

Composition du comité consultatif du Jeffery Hale – Saint Brigid’s: Mandat 3 ans : 2015-2018 - Jeffery Hale - Saint Brigid's (JHSB) (2015)

Always Leading From the Front, Alexander Gordon Wins Youth Leadership Award - Quebec Community Groups Network (QCGN) (2015)

Goldbloom Award Winners Bechervaise, Briand, Gatre Guemiri and Orr Know How To Get Things Done - Quebec Community Groups Network (QCGN) (2015)

New Award to Recognize Up and Coming Community Leaders - Quebec Community Groups Network (QCGN) (2015)

Quebec Community Groups Network Celebrates 20th Anniversary - Quebec Community Groups Network (QCGN) (2015)

The Thirty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2015)

The Build - Richardson, Mary (Council for Magdalen Islanders (CAMI), 2015)
This case study presents a project being implemented in the Baiedes-Chaleurs, Quebec, by which a group of elementary and high school students are building a sailboat with a teacher. They have the support of a broad range of community, institutional and non-for-profit partners who believe, like them, that a challenging project can have positive outcomes both inside and outside the classroom.

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2015)
Parallel title: Together we are Stronger

CLC Evaluation – The Quest for Sustainability & Best Practices : Final Report - Qu'anglo (2015)

CLC Evaluation – The Quest for Sustainability & Best Practices : Final Report : Executive Summary - Qu'anglo (2015)

QCGN Seeks Exceptional Individuals Who Contribute to Vitality of English-Speaking Community - Quebec Community Groups Network (QCGN) (2015)

ELAN to be Represented on Matv Advisory Committee - English Language Arts Network (ELAN) (2015)

Report : Community Network Forum - Community Health and Social Services Network (CHSSN) (2015)
Community organizations carry out their missions in an environment of continual reorganization of the health and social services system. In this context, groups must face the challenge of mobilizing resources to engage communities in a collective effort to commit the public system to meet the specific needs of community members. Groups are also challenged to introduce innovative approaches into their programs in a continual effort to achieve positive and long-lasting results.

Quebec Youth Lead the Way to Sesquicentennial Celebrations - Quebec Community Groups Network (QCGN) (2015)

Îles-de-la-Madeleine : Portrait de la communauté d'expression anglaise - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
Le présent portrait a été réalisé en collaboration avec de nombreux partenaires locaux, à l’initiative du Conseil des anglophones madelinots (CAMI) et avec l’appui du Réseau communautaire de santé et de services sociaux (RCSSS). Parmi les autres groupes ayant participé au processus figurent la Municipalité de Grosse-Île, l’école de Grosse-Île, la Corporation d’employabilité et de développement économique communautaire (CEDEC), le Centre scolaire communautaire (CSC) et l’Agglomération des Îles (comité de développement social/Les Îles en Forme).

Portrait of the English-speaking Community of Rouyn-Noranda - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed by Neighbours and the Community Health and Social Services Network (CHSSN), in collaboration with the Centre intégré de santé et des services sociaux (CISSS), the city of Rouyn-Noranda (Villes et villages en santé) and the local English school, Noranda School. Neighbours is a non-profit community organization established to serve the Englishspeaking population of the Rouyn-Noranda area through facilitating information sharing, defending the right of access to service in English and organizing social and cultural events. Neighbours is committed to strengthening networks within the English and French speaking population as well as encouraging community development initiatives. The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of Rouyn-Noranda in order to address the issues it faces.
Keywords: Official Language Minority Community (OLMC)

Portrait of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed in collaboration with many local partners, through the initiative of the Council for Anglophone Magdalen Islanders (CAMI), with support from the Community Health and Social Services Network (CHSSN). Other groups involved in this process include the municipality of Grosse-Ile, the Grosse-Ile school, the Community Economic Development and Employability Corporation (CEDEC), the Community Learning Centre (CLC), Agglomération des Îles (social development committee/Les Îles en Forme).

Portrait of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed in collaboration with many local partners, through the initiative of the Council for Anglophone Magdalen Islanders (CAMI), with support from the Community Health and Social Services Network (CHSSN). Other groups involved in this process include the municipality of Grosse-Ile, the Grosse-Ile school, the Community Economic Development and Employability Corporation (CEDEC), the Community Learning Centre (CLC), Agglomération des Îles (social development committee/Les Îles en Forme). The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of the Magdalen Islands in order to create a community development plan that addresses the issues it faces.

Annual Report : 2014-2015 - 4Korners (2015)

2014-2015 Funded Projects - Dialogue McGill (2015)

Projets financés 2014-2015 - Dialogue McGill (2015)

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Parallel title: School & Community Resources - Working Together is the Key!
Keywords: Official Language Minority Community (OLMC)

Rapport annuel de gestion : 2014-2015 - Jeffery Hale - Saint Brigid's (JHSB) (2015)
issued: 2014/2015

Building School-Community Partnerships : Together We can Make a Difference : CLC Initiative Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2015)

CLC Initiative Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2015)
Parallel title: Building School-Community Partnerships : Together We Can Make a Difference
Keywords: Official Language Minority Community (OLMC)

Professional Development in Education : Pushing the Boundaries of Possibility - Leading English Education and Resource Network (LEARN) (2015)
Number of pages: 324

Teacher Research : Integrating Action, Observation, and Reflection - Leading English Education and Resource Network (LEARN) (2015)
Number of pages: 362

Message For Our Veterans - Maurice, Cornella (2015)

Annual Report : 2014–2015 - NDG Community Council (NDGCC) (2015)

Rapport annuel : 2014–2015 - NDG Community Council (NDGCC) (2015)

Annual Report / Rapport annuel 2014-2015 - Quebec Community Groups Network (QCGN) (2015)
Keywords: Official Language Minority Community (OLMC)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2015)
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)
Number of pages: 24

Annual Report : 2014-2015 - Réseau de l’est de l’île pour les services en anglais (REISA) (2015)

The English-speaking Population of des Collines-de-l'Outaouais : a Community Portrait - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed by Connexions and the Community Health and Social Services Network (CHSSN), in collaboration with the Centre intégré de santé et de services sociaux des Collines de l’Outaouais (CISSSO). Connexions (the Connexions Resource Centre) is a not-for-profit community organization whose mission is to serve and promote the health, well-being and vitality of the English-speaking population of the Outaouais. It is committed to strengthening networks within the English and French speaking population as well as encouraging community development initiatives.

Annual Report 2014-2015 - Voice of English-speaking Quebec (VEQ) (2015)

Follow Your Fiction : A Poetry Anthology - Writers in the Community (2015)
Number of pages: 24